Análise da demanda de viagens atraídas por shopping centers em Fortaleza - Ary, Miguel Barbosa (2002)
Due to the significant amount of trips attracted to shopping centers, the fast increase in the number of these facilities in large urban areas has been of major concern for city planners and traffic engineers. In the last years, the legislati on of some Brazilian cities have dedicated special attention to traffic generator poles, requiring the development of assessment studies on the impacts caused by the implementation of such facilities over the transport system. With the objective of subsidizing the analysis of such a problem, in 1999 field surveys were carried out in six shopping centers in Fortaleza, in order to obtain local data for the characterization of trip demand regarding its generation, distribution and modal choice. In the analysisof these data, it was concluded that the traditional models, that consider a measure of the size as the only explanatory variable for forecasting the number of trips attracted to these facilities, are not appropriate to the local reality. It was observed that the demand attracted suffers the influence of several factors, such as locational and socioeconomic characteristics of the site impact area. Thus, based on the conclusions drawn from the case study, it was possible to develop a practical procedure foranalyzing the trip demand of future shopping centers in Fortaleza. It is believed that the present work has contributed for the evaluation of the impacts of shopping centers and other kinds of traffic generator poles, over the transport system of large Brazilian cities.